Features of the implementation of micro-interfaces in information systems - Stepanov, Oleksandr; Klym, Halyna (Видавництво Львівської політехніки, 2024)
Microservices are a software development technique, or variant of the service-oriented architecture structural style, that organizes an application as a collection of loosely coupled services. The purpose of the work is to study the methodology for the design and implementation of information systems using micro-interfaces in order to improve the quality and speed of their development and facilitate their use. The article proposes a method of transforming the software system architecture from monolithic to microservice architecture. A brief review of existing architecture reengineering research has been provided and the advantages of a microservice approach have been identified. At the second stage, a transition to a modular architecture with the allocation of functionality into separate modules has been proposed. An experiment with a typical external single page application demonstrates the performance of the proposed algorithm.
Keywords: Architecture; Interface; Micro-frontend; Microservices; Monolithic structure; Software applications